DAMPAK ISU MARKETPLACE GURU TERHADAP SEMANGAT BELAJAR MAHASISWA CALON GURU TANAH DATAR - Illahi, Dilsa Kurnia (Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Padangsidimpuan, 2023)
The purpose of this research is to determine the influence of prospective teacher students' interest in learning after hearing the issue of teacher market place. The research method used is descriptive quantitative method. The data collection instrument was carried out using a questionnaire or short questions regarding teacher marketplace issues circulating in the media. This research uses the Guttman scale with questions packaged in the Google Form application. The questions asked to prospective teachers are based on indicators of student teacher enthusiasm for learning. The research subjects were 73 prospective teachers in Tanah Datar. The results of the research explain that after the market place issue circulated, students remained enthusiastic about completing their studies, but many of the students' goals shifted. The implication that arises from the market place issue is that many prospective teacher students are disappointed with the issues coming out of the Minister of Education.Keywords: 3-5 keywords; Teacher market place; Promlematics of Indonesian education,; enthusiasm for learning